2017
DOI: 10.1007/s00204-017-1947-4
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of levamisole in cocaine users: a review and risk assessment

Abstract: The immunomodulatory adjuvant and antihelminth levamisole is increasingly used as an adulterant in cocaine worldwide. An accumulating body of clinical and toxicological literature has appeared since 2010 describing neutropenia, agranulocytosis, leukoencephalopathy and vasculitis in cases associated with levamisole-adulterated cocaine. Mostly, neutropenia and agranulocytosis were reported, characterized by a decimation of neutrophils. A large proportion of cases also involved vasculopathy, characterized by pron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
71
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 76 publications
0
71
0
Order By: Relevance
“…The first cases of toxicity due to the use of levamisole-tainted cocaine were reported in 2009 (39), and some studies already reported deaths as a result of complications secondary to this factor (32,33,(39)(40)(41). Multiple reports link the use of levamisoletainted cocaine to neutropenia, agranulocytosis, methemoglobinemia, and retiform purpura of the face and extremities (27,38,39,(41)(42)(43)(44)(45)(46)(47)(48)(49)(50).…”
Section: Cutting Agent Toxicitymentioning
confidence: 99%
“…The first cases of toxicity due to the use of levamisole-tainted cocaine were reported in 2009 (39), and some studies already reported deaths as a result of complications secondary to this factor (32,33,(39)(40)(41). Multiple reports link the use of levamisoletainted cocaine to neutropenia, agranulocytosis, methemoglobinemia, and retiform purpura of the face and extremities (27,38,39,(41)(42)(43)(44)(45)(46)(47)(48)(49)(50).…”
Section: Cutting Agent Toxicitymentioning
confidence: 99%
“…21 Further, the pharmacological profile of dexamisole resembles in some respects that of tricyclic antidepressants. 22 In most countries, levamisole and tetramisole have been withdrawn from the market for medical treatment of humans due to serious adverse neurological, immunological, and inflammatory effects. In the past, it was also used as an immunostimulant in humans in the treatment of rheumatoid arthritis, AIDS, colorectal cancer, and nephrotic syndrome, for example.…”
mentioning
confidence: 99%
“…21 Nowadays, levamisole is predominantly used as anthelminthic in veterinary medicine. 10,22,23 In spite of the potential harmful effects, biological specimens, such as blood or urine, are rarely tested for levamisole/tetramisole in forensic and clinical toxicology. 22 In most countries, levamisole and tetramisole have been withdrawn from the market for medical treatment of humans due to serious adverse neurological, immunological, and inflammatory effects.…”
mentioning
confidence: 99%
“…Cutaneous vasculitis with retiform purpura secondary to cocaine contaminated with levamisole has been well described in the literature . We report the first case of erythema elevatum diutinum (EED)‐like vasculitis secondary to levamisole exposure.…”
mentioning
confidence: 92%
“…Levamisole is a synthetic imidazothiazole used as a cocaine‐bulking agent, which has been found in 66% of the cocaine supply in the US . Originally introduced as an anti‐helminthic drug and later found to have immunomodulatory properties, levamisole was eventually removed from the US market because of severe side effects, including agranulocytosis . LIV has been well described.…”
mentioning
confidence: 99%